CUSTOMARY DIVORCE PRACTICES IN THE PANYABUNGAN SOCIETY: A REVIEW OF ISLAMIC LAW - Edi, Sabrun; Ritonga, Raja; Dongoran, Irham (Islamic Circle, 2022)
In the Panyabungan community, customary law plays a strong role in regulating various aspects of life, including matters of divorce. However, these customary practices often do not align with the provisions of Islamic law, which has strict principles regarding divorce. This study aims to understand how customary divorce is practiced, the reasons for divorce recognized by customary law, and to compare these with the regulations of divorce in Islamic law. The approach used is qualitative with a descriptive-analytical method. Data were collected through field observations, interviews with customary leaders and the community, as well as literature reviews related to Islamic law and customary practices. The results of the study indicate that although there are similarities in some basic principles, such as the mutual consent of both parties, there are significant differences in the procedures and reasons for divorce between customary law and Islamic law.